Perkembangan Ekspor Minyak Kelapa Sawit (Crude Palm Oil) Indonesia - Yumna, Hartsa Fayi; Perdana, Putra (Peneliti.net, 2023)
This research provides a comprehensive overview of the development of both the import and export of Crude Palm Oil (CPO), aiming to demonstrate the potential and contribution of the Palm Oil industry in Indonesia. The study employs a quantitative descriptive research design. The focus of the research is on the export development over a one-year period from March 2022 to March 2023. The data used in this study are secondary data obtained from the Central Bureau of Statistics (BPS), Trademap, and the Indonesian Palm Oil Association (GAPKI). After analyzing the data, it is evident that Palm Oil is a crucial commodity for Indonesia. However, the export of Palm Oil in Indonesia experienced a decline during the period from March 2022 to March 2023. Sumatra is the island with the largest production and land area for Palm Oil in Indonesia. Additionally, India is the primary export destination for Indonesian Palm Oil.